Toward ultra-thin and omnidirectional perovskite solar cells: Concurrent improvement in conversion efficiency by employing light-trapping and recrystallizing treatment. (June 2019) - Wang, Fengyou; Zhang, Yuhong; Yang, Meifang; Fan, Lin; Yang, Lili; Sui, Yingrui; Yang, Jinghai; Zhang, Xiaodan
Abstract : Efficient perovskite solar cells with ultra-thin absorber would be very attractive for semitransparent-, tandem-, and flexible-photovoltaic application. However, the absorber with ultra-thin thickness always cause extra optical losses due to the insufficient light-harvesting. Here, we try to stress this key factor by constructing textured substrates and appropriate control of recrystallization treatment for ultra-thin perovskite solar cells that synergizes the merits characters including good broad-band, enhanced light-trapping and excellent separation/collection of photo-generated charges. In particularly, the isopropanol (IPA) - assisted recrystallizing treatment enable to form pinholes free perovskite films on a high-aspect-ratio substrate, which relax the trade-off between the optical enhancements and electrical deteriorations. The perovskite solar cell exhibits an efficiency of 18.6% by using an only ∼200-nm MAPbI3 as the absorber, which is a record efficiency for such thin-perovskite solar cells. We also exhibit the solar cells that shows the enhancement of daily generated power to 47.6% by using the crater-like architecture, as compared to traditional planar devices. The concurrent enhancement in optical and electrical performance for achieving high-efficiency perovskite solar cells with thin absorber demonstrated here makes a simple process promising for photoelectric device application. Graphical abstract: Image 1 Highlights: Quasi-omnidirectional perovskite solar cell with ultra-thin absorber has been prepared. Efficient light trapping has achieved by employing crater-textured substrates. Interface defects have been effectively eliminated by the proposed recrystallizing treatment. A high efficiency of 18.6% have been achieved for ∼200 nm perovskite solar cells.